PENERAPAN KONSEP SENTRALITAS PADA KERATON SURAKARTA HADININGRAT - Denny Winata; Indri Astrina (Riset Arsitektur (RISA), 2022)
Abstract - Keraton is a term to describe a place where Javanese ruler and his family lives. Keraton, which regarded as a historical building, holds an important role in development of a Javanese city. Entitled not only as a home for the ruler, the impact it embodies are also in effect of lives of the people such as in administrative sector. Keraton nowadays no longer be regarded as a governmental entity. As Indonesia has declared its independence, the function of a keraton changes into a building that tells history of its era, a building which has richness of history, culture, and religious insight. This gives keraton a new role as the center of knowledge and spiritual. Keraton Surakarta Hadiningrat is one of Javanese keratons that still being used. No longer as a center of government, this keraton, inhabited by the current Surakarta ruler SISKS Pakubuwono XIII, was a legacy of The Mataram Kingdom. As central entity of multiple circumstances, keraton fulfils the role it has in functional and architectural aspects. Nevertheless, the objective of this research is to identify and classify the architectural mass order of Keraton Surakarta Hadiningrat including the role of centrality that embodies in it. Qualitative research method using the descriptive and textual analysis approach is utilized to describe the concept of centrality that keraton has. Architect and design theorist, Christopher Alexander, develops the ideology of centrality which is then integrated with the cosmology concept Keraton Surakarta Hadiningrat has been built upon. This is to evoke the ground reason on why certain order has been used in the building complex of keraton, a centrality-driven architecture. Data have been gathered through site observation and literature references. Those are being categorized into two analytical focus group which are relation between keraton and the city of Surakarta (macro scale) and seven layers of Jambudvipa in keraton including Keraton’s Javanese vernacular roof (micro scale). Research foundings prove that keraton had a crucial role in a city planning from the implementation of Catur Gatra Tunggal concept apparent in Javanese city planning. Historical and cultural foundings dictate credibility on how Surakarta was developed after the existence of keraton. Foundings that emphasize on the concept of centrality reveal that there are significant intensity differences in a keraton. This is related to the functional and contextual location regarding the cosmology concept. The foundings also enlighten that the order of buildings in keraton are based on single, main hierarchy to the Kedhaton which is the heart of keraton. It is shown that although keraton has small centrality existence throughout the imaginary layers of Jambudvipa, the entity of small centrality elements reaffirms the main role of Kedhaton as well as strengthen its central quality. The bond and relationship of each layers are extremely strong in keraton. Key Words: centrality, order, keraton, cosmology, Surakarta, East Java